KUALITAS PELAYANAN DI KANTOR KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - jurnalmap map; Sy. Dewi Marisa; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This study aims to describe the quality of service in the Mandah District Office of Indragiri Hilir Regency. The method used in this research is descriptive qualitative researched only one variable about the quality of service. The results of the study are based on the quality dimension which consists of: Tangibles, the community states that the officers in providing services are quite good with neatly dressed and polite. Physical facilities such as waiting rooms are quite comfortable, queues are very organized, thus speeding up the service process. Reliability is quite good, that is, the community is easy and the process of arranging services is not complicated. Responsiveness of employees to criticism and complaints of the community, responded well and immediately followed up. Besides that, employees are present at the service office on time, so that if there are people who come directly served well. Assurance is discipline, courtesy and friendliness of employees is quite good as evidenced by the service users who come welcomed by employees to ask things they can help. Empathy of employees who include attention to the community who come to the public service unit asked their needs and provide explanations that are easily understood by the community at large. Keywords: service quality